Geography and ethics II: Emotions and morality. (December 2016) - Olson, Elizabeth
In this second report, I consider the relationship between emotion and morality from a geographical perspective. Though traditional and contemporary engagements in moral philosophy and psychology offer a diverse range of theories and approaches to emotions and morality, few of these explicitly consider or incorporate the role of space. I consider theories of embodiment and relationality as one means through which emotions become collective and institutionalized, with a focus on emotional geographies and care. I conclude by reflecting on political emotions as conflictive but insightful signals of societal shifts in our moral emotions, and suggest that incorporating emotions may also provide a different way of thinking about the problem of distant care.